Population, Sample (Quantitative) and Selection of Participants/Key Informants (Qualitative) - Sukmawati Sukmawati; Salmia Salmia; Sudarmin Sudarmin (Edumaspul: Jurnal Pendidikan, 2023)
Research using a population, if the population is large and it is impossible for the reviewer to examine everything in the population, due to limited funds, manpower and time, the reviewer may use samples taken from a representative population. The study sample is part of the population taken as a data source and can represent the entire population. Disproportionate Stratified Random Sampling Technique Group Sampling (Area Sampling) The area sampling technique is used to determine the sample when the object being studied or the data source is very large. To determine the object used as a data source, sampling is based on the specified population area. In a qualitative study, informants were divided into three, namely: key informants, main informants, and supporting informants. Key informants are informants who have comprehensive information about the issues raised by investigators. The selection of informants in a qualitative study is determined entirely by the reviewer, which is why it is called purposive sampling, namely choosing information-rich cases based on the strategy and objectives set by the reviewer whose numbers depend on the objective and learning resources.